In search of the big fish: investigating the coexistence of the big-fish-little-pond effect with the positive effects of upward comparisons. - Seaton, M; Marsh, H; Dumas, F; Huguet, P; Monteil, J; Régner, I; Blanton, H; Buunk, A; Gibbons, F; Kuyper, H; Suls, J; Wheeler, L (2008)
Blanton, Buunk, Gibbons, and Kuyper (1999) and Huguet, Dumas, Monteil, and Genestoux (2001) found that children nominated a social comparison target who slightly outperformed them in class with a beneficial effect on course grades - an assimilation effect, but with no effects on self-evaluation. However, big-fish-little-pond effect (BFLPE) research has shown that attending a high-ability school has a negative effect on academic self-concept--a contrast effect. To resolve this apparent conflict, the present investigation (1) tested the BFLPE in the Netherlands and France, using nationally representative samples (Study 1) and (2) further analysed (using more sophisticated analyses) the Dutch (Blanton et al.) study (Study 2) and the French (Huguet et al.) study including new French data (Study 3), to examine whether the BFLPE coexisted with, or was moderated by, the beneficial impact of upward comparisons. In support of the BFLPE, all studies found the negative effects of school- or class-average ability on self-evaluation, demonstrating that these assimilation and contrast effects can coexist.